Beta-3-adrenergic receptor Trp64Arg polymorphism: does it modulate the relationship between exercise and percentage of body fat in young adult Japanese males? - Nakashima, Hiroshi (Springer Japan, 2013)
OBJECTIVES: The Trp64Arg polymorphism of the beta-3-adrenergic receptor gene has been studied as a potential genetic factor contributing to the development of obesity. Several studies have investigated whether or not this polymorphism affects weight reduction due to exercise, but the results of these studies have not been consistent. Moreover, information on a population characterized by a wide ranges of physical activities is scarce. Thus, to further understand the impact of this polymorphism, we examined whether the polymorphism modulates the relationship between physical activity due to exercise (PAE) and percentage of body fat (%BF). METHODS: The study population was 70 Japanese male young adults with a high prevalence of habitual exercise. PAE was estimated by a questionnaire, and %BF was measured by bioelectrical impedance analysis. Genotyping was done by PCR–restriction fragment length polymorphism analysis. RESULTS: The median PAE value of the subjects was 6.9 MET-h/day with an interquartile range of 1.5–10.3 MET-h/day. PAE correlated significantly with %BF in the entire population and within the two subpopulations, namely, carriers or non-carriers of the Arg allele. Multiple regression analysis of PAE, Trp64Arg polymorphism, and the interaction term revealed that while the PAE-derived independent variable was statistically significant, the interaction term was insignificant. When the two regression lines of subjects with and without the Arg allele were considered, the difference between the two slopes did not deviate from zero, nor did the vertical distance of the two regression lines. These findings suggest that the impact of this polymorphism is limited. CONCLUSIONS: In our study population of young adult Japanese males, the impact of the Trp64Arg polymorphism on the association between exercise and body composition was weak, if it existed at all.